2020
DOI: 10.1029/2020gl090737
|View full text |Cite
|
Sign up to set email alerts
|

Southern Ocean Upwelling and the Marine Iron Cycle

Abstract: The iron (Fe) supply to phytoplankton communities in the Southern Ocean surface exerts a strong control on oceanic carbon storage and global climate. Hydrothermal vents are one potential Fe source to this region, but it is not known whether hydrothermal Fe persists in seawater long enough to reach the surface before it is removed by particle scavenging. A new study (Jenkins, 2020, https://doi.org/ 10.1029/2020GL087266) fills an important gap in this puzzle: a helium-3 mass balance model is used to show that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Our study suggests that the residence time for hydrothermal Fe is on the order of a few tens of years, which requires upper ocean ventilation to be sufficiently rapid. The conservative hydrothermal tracer 3 He has been estimated to emerge in Southern Ocean surface waters within 99 ± 18 years (Jenkins, 2020), similar to the median re-exposure timescale from the deep Southern Ocean calculated from data constrained ocean physical models (DeVries and Holzer, 2019;Weber, 2020). Estimates from particle tracking models at higher spatial resolution suggest more rapid ventilation timescales of around 20 years, which slow to many decades in coarser resolution configurations (Tamsitt et al, 2017;Drake et al, 2018).…”
Section: Wider Implicationssupporting
confidence: 57%
“…Our study suggests that the residence time for hydrothermal Fe is on the order of a few tens of years, which requires upper ocean ventilation to be sufficiently rapid. The conservative hydrothermal tracer 3 He has been estimated to emerge in Southern Ocean surface waters within 99 ± 18 years (Jenkins, 2020), similar to the median re-exposure timescale from the deep Southern Ocean calculated from data constrained ocean physical models (DeVries and Holzer, 2019;Weber, 2020). Estimates from particle tracking models at higher spatial resolution suggest more rapid ventilation timescales of around 20 years, which slow to many decades in coarser resolution configurations (Tamsitt et al, 2017;Drake et al, 2018).…”
Section: Wider Implicationssupporting
confidence: 57%
“…In the subarctic North Atlantic and North Pacific Ocean, where dust provides 15%–50% of the Fe demand, additional Fe may be transported through western boundary currents from regions of high deposition. Near the Antarctic coastline in the Southern Ocean, shallow shelves (Abadie et al., 2017) and upwelling deep water carrying hydrothermally sourced Fe (Jenkins, 2020; Resing et al., 2015; Weber, 2020) may provide the additional Fe required to support export. In the Tropical and Eastern Pacific, where the Fe supply from dust falls furthest short of the demand (<10%), upwelling of sediment‐sourced Fe, especially from oxygen minimum zones (John et al., 2018), may make up the deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations using a helium‐3 mass balance model indicated that upwelling of hydrothermal dFe from deep waters may occur over a ∼100‐year period (Jenkins, 2020; Weber, 2020). However, these estimates are subject to scavenging times of dFe that span several orders of magnitude (Bergquist & Boyle, 2006; Weber, 2020). The generally lower dFe concentrations in CDW of the Antarctic zone compared with that of the subantarctic zone (Figure 3c) indicated that this hydrothermal source may have a greater impact on subantarctic waters.…”
Section: Discussionmentioning
confidence: 99%
“…Tagliabue et al (2022) suggested that dFe enriched CDW from this hydrothermal activity may influence southern surface water dFe concentrations due to the shoaling of CDW approaching the Antarctic continental shelf (Figure 2). Investigations using a helium-3 mass balance model indicated that upwelling of hydrothermal dFe from deep waters may occur over a ∼100-year period (Jenkins, 2020;Weber, 2020). However, these estimates are subject to scavenging times of dFe that span several orders of magnitude (Bergquist & Boyle, 2006;Weber, 2020).…”
Section: Bathypelagic 1000-2000 M Depthmentioning
confidence: 99%